Cloud Computing in Advancing Intelligence Capabilities for Indonesia National Security, Literature Review Study - Meliala, Brandon Nathanael (Universitas Komputer Indonesia, 2025)
Cloud computing has emerged as a transformative technology that enhances intelligence capabilities and supports national security operations in the digital era. This study aims to examine the role of cloud computing in strengthening Indonesia’s intelligence infrastructure through a literature review approach. The research analyses existing academic studies, policy reports, and technological frameworks related to cloud-based systems in intelligence management, data processing, and information sharing. The findings indicate that cloud computing enables faster data integration, scalable storage, real-time analytics, and improved inter-agency collaboration, which are essential for effective intelligence gathering and decision-making. However, the adoption of cloud technology in national security also raises challenges, including cybersecurity risks, data sovereignty concerns, and regulatory limitations. The study concludes that strategic implementation of secure cloud architectures, supported by robust policies and institutional capacity, can significantly enhance Indonesia’s intelligence capabilities while maintaining data protection and national security resilience.